A sinusoidal nonlinear oscillator with adjustable frequency - Hanmeng, Nithima; Pranayanuntana, Poramate (My University, 2009)
A sinusoidal nonlinear oscillator with adjustable frequency was studied. The frequency of oscillation was adjusted via the change of the center frequency of the second order band-pass filter, while keeping the quality factor constant. The describing function method was used to predict the limit cycles and to analyze the stability of oscillation. The proposed circuit consisted of two important parts in the feedback connection configuration: an operational transconductance amplifier (OTA) as a nonlinear element in feedback path; and a bandpass filter in the feedforward path. The experimental results were simulated by the ORCAD CAPTURE and MATLAB computer programs.
Keywords: Describing function; Frequency adjustment; Nonlinear oscillator; OTA